Introduction to the Africa Fertilizer and Soil Health Action Plan - African Union Development Agency- NEPAD; African Union (2024)
This brief introduces the Africa Fertilizer and Soil Health (AFSH) Action Plan. It provides context to the AFSH Action Plan describing it as a key outcome of the AFSH Summit and highlighting Africa’s challenges surrounding land degradation, climate change and food insecurity. Further, it provides the AFSH Action Plan results chain, and the goals expected to be achieved in the first ten years of implementation (2024-2034).